Impact of acute left ventricular apical thrombus on cardioversion for atrial fibrillation. Issue 11 (24th September 2017) - Vaidya, Vaibhav R.; Prueksaritanond, Suartcha; Bois, John P.; Nadipalli, Abhinav; Borgeson, Daniel D.; Melduni, Rowlens M.
Abstract : Among patients undergoing cardioversion for atrial fibrillation, the presence of left ventricular thrombus is a relatively uncommon and challenging clinical dilemma. While left atrial appendage thrombus is a contraindication to cardioversion, there is paucity of data regarding the safety of cardioversion in with the presence of left ventricular apical thrombus. Also, thrombus characteristics such as protrusion and mobility on echocardiography are known risk factors for systemic embolism. In this article, we present a case highlighting the management of atrial fibrillation in the setting of left ventricular dysfunction, acute heart failure, and echocardiographic evidence of acute left ventricular apical thrombus.